Initial Discoveries from the Rhizoliths Petrified Forest of Chania - Emmanouil Manoutsoglou (Heritage, 2025)
This study presents the initial scientific characterization of the recently discovered Rhizoliths Petrified Forest of Chania, located at Stavros in the Akrotiri peninsula of Crete, Greece. Unlike most known petrified forests that primarily preserve tree trunks, this site uniquely features an abundance of rhizoliths—fossilized root systems preserved through calcium carbonate mineralization. The rhizoliths exist within aeolianite formations along the coastal front, with diverse morphologies and sizes ranging from small trace-like forms to massive, branched structures exceeding one meter in length. The rhizoliths are exposed within historic Venetian quarries that operated from Minoan times through the medieval period at Stavros Bay, where quarrying operations have revealed these fossilized root systems preserved in coastal dune deposits. The site also contains in situ petrified trunks, calcrete formations, and biokarstic dissolution features that further enhance its scientific value. Microscopic examination of rhizolith samples has revealed valuable information about their internal structure, showing clear biogenic characteristics. The preservation of rhizolith structures and associated sedimentary features provides valuable insight into the Quaternary paleoenvironment, including former vegetation patterns, soil stabilization processes, and paleoclimatic conditions. The alternating layers of aeolianites and paleosols suggest cyclical environmental changes, with periods of active dune formation alternating with more stable conditions allowing soil development and vegetation establishment. This study documents the Stavros rhizoliths and their paleoenvironmental significance, contributing to the comparative understanding of similar features documented at other global sites.